Flow analysis of second grade fluid with wall suction/injection and convective boundary condition - Aman, Sidra; Mohd Zuki, Salleh; Zulkhibri, Ismail; Khan, Ilyas (Penerbit Akademia Baru, 2019)
Analysis of unsteady heat and mass transfer in second grade fluid over a flat plate with wall suction and injection is considered. Mixed convection, convective boundary conditions and oscillating wall starting from rest are deliberated. Some suitable variable transformations are introduced for the reduction of partial differential equations to ordinary differential equations. Then the model is tackled using a combination of Laplace transform, the perturbation technique and numerical inversion of Laplace transform is implemented to obtain the semi analytical solutions for momentum, heat and concentration. Graphical presentation is illustrated for the ingrained parameters to shed light on the physical insight of the flow, heat and mass transfer of the fluid. Velocity of the fluid maximizes with increasing values of Grashof number due to dominant buoyancy effects. Finally, comparison has been made between the results of two algorithms (Tzou and Stehfest’s algorithm).